Through fire and flames: post-burning survival and detection of dismemberment-related toolmarks in cremated cadavers - Tutor, Pilar Mata; Márquez-Grant, Nicholas; Villoria Rojas, Catherine; Muñoz García, Alexandra; Pérez Guzmán, Inés; Benito Sánchez, María (Springer, 2020)
During a homicide investigation in which fire has been used to reduce the size of the cadaver and conceal the evidence of injuries, the identification of perimortem trauma presents a challenge, in particular in cases when the perpetrator has dismembered the body followed by burning the remains. It is therefore important to understand the effects which heat causes on fresh bone. The aim of this paper is to perform a pilot study on the survival ratio of toolmarks in different anatomical regions associated with dismemberment, and a descriptive analysis of the variables that may potentially influence the post-burning survival and detection. To achieve this, three donated embalmed cadavers were used to simulate a case in which an attempted dismemberment and burning had occurred. Fifty-five pre-burning injuries were manually induced: 30 using a machete to inflict chopping trauma, and 25 with a serrated bread knife to inflict sharp force trauma, on the thigh, knee, ankle and wrist. The cadavers were cremated in a furnace at Madrid’s Cementerio Sur and the burnt remains were analysed at the Laboratorio de Antropología y Odontología Forense of the Universidad Complutense de Madrid. Not all pre-burning injuries inflicted were visible after the cremation process; only 13% were detected in this experiment. Toolmarks can be masked, modified, destroyed or overlooked from the outset of the procedure due to several factors which influence the post-burning survival and detection of toolmarks and contribute to conceal the evidence of trauma. Additional research should be done to study further variables which affect the post-burning visibility of sharp force trauma.
Keywords: Forensic anthropology; Dismemberment; Sharp force trauma; Pre-burning trauma; Cremated human remains